The National Economy and its Efficiency: Specialization, Economic “Oases” and Regional Clusterization - Melnikas, Borisas (Ekonomika, 2004)
The problems and priorities of increasing the efficiency and competitiveness of national economies are described and analyzed. Regional specialization and development of a network of clusters as the main directions of social and economic development are discussed. The most important problems: development and modernization of national economies under conditions of globalisation and market internationalisation; national economy as a system and as an integral entity of economic activities. The most important priorities: formulation of principles of increasing the efficiency and competitiveness of national economies; formulation of priorities in economic development strategies, especially for transition countries; development of the idea of “oazes” as a system of special conditions for social economic growth; concrete solutions for the innovation activities in Lithuania, other Baltic and other Central and East European countries. The idea of “oases” as a new form of clusterization is described.